Proses Penerbitan Dokumen Pemberitahuan Pabean Free Trade Zone (PPFTZ) melalui Sistem Bea dan Cukai Batam oleh PT. Natio Bahari Agensi - Michael Melpianus; Fadiyah Hani Sabila (Jurnal Transformasi Bisnis Digital, 2024)
This paper explains the process of issuing free trade zone (PPFTZ) customs notification documents through the Batam PT customs and excise system. Natio Bahari Agency Batam. The methods used in this observation are field research and interviews where the author obtains material or paper materials directly from the field and interacts directly with people who have an interest in the world of document publishing, both officers and fellow agents, apart from that. The author also met directly with relevant sources who were interested in the subject matter taken from PT. Natio Bahari Agensi which is one of the companies operating in the field of agency and Financial Services Customs Entrepreneurs. PT Natio Bahari Agensi Batam Serves various types of vessels ranging from tugboats, Dredger barges, to offshore vessels in Batam Harbor. In the document management system, the system used is the CEISA-PPFTZ system. After the Commercial Invoice and Packing List is received by the PPJK from the importer or exporter, it can be continued by carrying out the process of submitting a new document registration number in the CEISA system until an Approval Letter can be issued. Goods Release (SPPB) or Goods Release Service Note (NPPB). The purpose of this research paper is to find out how the process of issuing Free Trade Zone Customs Notification Documents in the Batam Special CEISA System by PT. Natio Bahari Agency Batam. There are still various obstacles experienced in processing documents, such as network problems in the system which cause difficulties in inputting data in the system, delays in sending supporting documents by exporters and importers, and so on.